Analyzing performance in service organizations - Sherman, H. David; Sherman, H. David (MIT Sloan Management Review, 2013)
Just as sports teams have increasingly relied on rigorous quantitative analyses, so have many businesses. In particular, a growing number of service organizations have been investigating the use of a sophisticated linear programming technique called DEA, or data envelopment analysis. (In this article, the authors use the term "balanced benchmarking" to denote DEA.) The technique enables companies to benchmark and locate best practices that are not visible through other commonly used management methodologies. Today, balanced benchmarking can be used by anyone with Microsoft Excel, but it was not always so easy. When it was first introduced in the 1980s, balanced benchmarking was an academic tool for measuring and managing relative efficiency of peer organizations. Balanced benchmarking simultaneously considers the multiple resources used to generate multiple services, along with the quality of the services provided. It also provides managers with a sophisticated mechanism to assess the performance of different service providers - comparing, for example, the London and Tokyo offices of a global advertising agency - by going well beyond crude metrics and ratios such as profitability and account billings per employee. A company can identify its least efficient offices or business units, and it can assess the magnitude of the inefficiency and investigate potential paths for improvement. Moreover, executives can study the top-performing units, identify the best practices and transfer that valuable knowledge throughout the organization. Lastly, balanced benchmarking enables companies to test their assumptions, particularly before implementing initiatives that might inadvertently be counterproductive.